Impact of COVID-19 on woodfuel value chains in the DRC: Addressing risks and vulnerabilities of operators and end-users - Schure, J.; Kasereka-Muvatsi, L.; Cerutti, P.O.; Sola, P. (Center for International Forestry Research, 2021)
The COVID-19 pandemic, including the health impacts of the virus itself and measures to contain and mitigate them, has far-reaching impacts on economies, value chains and livelihoods. The pandemic has revealed the extent of vulnerability in our societies to risks and shocks. Indeed, most of these vulnerabilities were triggered or amplified by the crisis or its responses